Deconstructing Martial Arts - Bowman, Paul (Cardiff University Press, 2019)
"What is the essence of martial arts? What is their place in or relationship with culture and society? Deconstructing Martial Arts analyses familiar issues and debates that arise in scholarly, practitioner and popular cultural discussions and treatments of martial arts and argues that martial arts are dynamic and variable constructs whose meanings and values regularly shift, mutate and transform, depending on the context. It argues that deconstructing martial arts is an invaluable approach to both the scholarly study of martial arts in culture and society and also to wider understandings of what and why martial arts are. Placing martial arts in relation to core questions and concerns of media and cultural studies around identity, value, orientalism, and embodiment, Deconstructing Martial Arts introduces and elaborates deconstruction as a rewarding method of cultural studies."